Law Enforcement on Criminal Acts of Village Fund Corruption in Padangsidimpuan City (Study of Decision Number 104/Pid.Sus-TPK/2024/PN Mdn) - Sahreni Simanjuntak; Ramadhany Nasution; Winta Hayati (SEAN Institute, 2026)
This research is motivated by the rampant criminal acts of Village Fund corruption which have resulted in state financial losses, hampered development, and decreased public trust, especially in Padangsidimpuan City. This study aims to analyze the forms and modus operandi of Village Fund corruption, identify the causal factors, and examine the judge's legal considerations in Decision Number 104/Pid.Sus-TPK/2024/PN Mdn. The method used is a normative juridical approach and empirical juridical through literature studies, analysis of laws and regulations, and case studies by examining court decisions, trial facts, and witness statements. The results of the study indicate that the corrupt practice was carried out through a cut in the allocation of funds by 18% by certain officials, which resulted in a state loss of Rp427,150,000. The defendant was proven to have violated Article 3 of the Corruption Eradication Law and was sentenced to five years' imprisonment with a fine and compensation. The main contributing factors include weak supervision, low apparatus capacity, lack of transparency, and minimal public participation. The conclusion is that law enforcement needs to be strengthened firmly and comprehensively through increased oversight, apparatus capacity, and community involvement, thereby creating a deterrent effect and encouraging transparent and accountable Village Fund governance for the welfare of village communities. These findings have important implications for the development of anti-corruption policies at the village level and strengthening coordination among law enforcement officials. They can also serve as a practical reference for improving village financial management systems with integrity and sustainability in the future. Furthermore, this study emphasizes the urgency of public education and digitalization of oversight to prevent irregularities early on in a systematic and measurable manner.